2017
DOI: 10.1111/sms.12979
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of music tempi and intensities on grip strength and subjective affect

Abstract: Pretask music is widely used by athletes albeit there is scant empirical evidence to support its use. The present study extended a line of work into pretask music by examining the interactive effects of music tempo and intensity (volume) on the performance of a simple motor skill and subjective affect. A 2 × 2 within-subjects factorial design was employed with an additional no-music control, the scores from which were used as a covariate. A sample of 52 male athletes (M = 26.1 ± 4.8 years) was exposed to five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 31 publications
(65 reference statements)
2
41
0
Order By: Relevance
“…Pre-task music has been successfully used as a stimulant [21], and such benefits may contribute to the ergogenic effects identified in empirical studies. These effects include improved strength [22] and improved endurance, such as in a 500 m rowing test [23] or in a 25-min submaximal cycling test [24]. However, other research found no improvement in athletes' performance when running at 90% of maximum VO 2 [25] or in performance in three consecutive sprints by bike [26], It has also been suggested that the timing and type of music might affect anaerobic performance response [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Pre-task music has been successfully used as a stimulant [21], and such benefits may contribute to the ergogenic effects identified in empirical studies. These effects include improved strength [22] and improved endurance, such as in a 500 m rowing test [23] or in a 25-min submaximal cycling test [24]. However, other research found no improvement in athletes' performance when running at 90% of maximum VO 2 [25] or in performance in three consecutive sprints by bike [26], It has also been suggested that the timing and type of music might affect anaerobic performance response [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…In the same line, Fucci (1993) demonstrated that, when a number of musical excerpts are played at the same sound pressure level, well-liked fragments can be perceived as less loud compared to the lesser preferred. In research by Karageorghis et al. (2018), main effects of the intensity of pretask music on affective valence were retrieved, suggesting that athletes perceive loud music as more pleasurable compared to less intense sounds.…”
Section: Musical Intensity As a Tool To Boost Performance: Evidence Amentioning
confidence: 99%
“…Yet, pretask music is widely used by athletes as well. Karageorghis et al. (2018) explored the impact of tempo and intensity of music presented prior to the exercise, focusing on grip strength and subjective affect (valence and arousal).…”
Section: Musical Intensity As a Tool To Boost Performance: Evidence Amentioning
confidence: 99%
“…While the central control process underlying grip style management is non-conscious [30], grip force excess can be made accessible to immediate awareness of the user during an intervention. Thus, multi-sensor real-time grip force sensing by wearable systems can directly help to prevent incidents or tissue damage during interventions when it includes a procedure for sending specific visual or auditory signals [28][29][30][31][32][33] to the operator or surgeon whenever his/her grip force exceeds a critical limit.…”
Section: Discussionmentioning
confidence: 99%